The Interactive Effect of Diabetes Family Conflict and Depression on Insulin Bolusing Behaviors for Youth - Maliszewski, Genevieve (J Diabetes Sci Technol, 2016)
OBJECTIVE: Adherence to type 1 diabetes management declines as children enter adolescence. For youth, psychosocial variables including mood and interpersonal relationships play a large role in diabetes maintenance. The current study assessed the unique and interactive roles diabetes family conflict and depression have on insulin bolusing behaviors for youth ages 10-16 years. METHODS: Ninety-one youth-parent dyads completed a survey assessing family conflict and depression. Mean daily blood glucose levels, mealtime insulin bolus scores (BOLUS), and glycated hemoglobin (HbA1c) were collected from the medical record as outcome variables. RESULTS: Parent-reported diabetes-related family conflict and youths’ endorsed depression both significantly predicted insulin bolusing behavior, R(2) = .13, F(2, 88) = 6.66, P < .05. The interaction of diabetes family conflict and youth depression played a significant role in youths’ bolusing behaviors, above and beyond that which was predicted by conflict and depression separately, R(2) = .18, F(change)(1, 87) = 4.63, P < .05. BOLUS was negatively related to youths’ hemoglobin A1c, r = –.556, P < .001 and mean daily blood glucose levels, r = –.428, P < .001. CONCLUSIONS: Among depressed youth, mealtime insulin BOLUS scores declined with greater diabetes-related family conflict, while there was no change in BOLUS scores among depressed youth living in families reporting less conflict. Findings underscore the importance of screening for depression and family conflict in youth experiencing or at risk for poor adherence to mealtime insulin and higher HbA1c levels.